The quality and reliability of TikTok videos on non-alcoholic fatty liver disease: a propensity score matching analysis - Lai, Yongkang; He, Zixuan; Liu, Yilong; Yin, Xiaojing; Fan, Xuanming; Rao, Ziang; Fu, Hongyu; Gu, Lun; Xia, Tian (Frontiers in Public Health, 2023)
Background: Lifestyle modification is the cornerstone of nonalcoholic fatty liver disease (NAFLD) prevention and treatment. Short video platforms can facilitate easier access to health information for patients, thereby influencing lifestyle changes. An increasing number of individuals rely on online platforms to acquire health-related information about non-alcoholic fatty liver disease. However, the quality of information regarding non-alcoholic fatty liver disease on these platforms remains unclear. Objective: This study aimed to investigate the quality of information about NAFLD on TikTok. Methods: A total of 497 videos were retrieved from TikTok. The basic video information including video source was extracted. Two independent raters evaluated the quality and reliability of the videos using the Global Quality Score system and modified DISCERN tool. Propensity score matching (PSM) was used to compare video quality across sources. Results: NAFLD-related videos on TikTok were divided into three groups according to the uploader: health professionals, medical institutions, and science bloggers. Overall, the quality of NAFLD videos on TikTok was not satisfactory. Before PSM, there were no significant differences in video quality and content between the three groups. After PSM, the quality of NAFLD videos from health professionals was significantly better than the videos created by other groups. Besides, the videos of health professionals outperformed those of medical institutions and science bloggers in terms of the definition of disease, risk factors, and treatment, but were inferior to medical institutions considering the symptoms and tests of NAFLD. Conclusion: The quality of NAFLD-related videos on TikTok needs improvement. Compared with videos created by science bloggers and medical institutions, videos from health professionals may provide more correct guidance on the treatment and prevention of NAFLD.